Remote sensing as a tool for bathymetric mapping of coral reefs in the Red Sea (Hurghada – Egypt) - Tony Vanderstraete; Rudi Goossens; T.K. Ghabour (Belgeo)
For monitoring coral reefs, a bathymetric map is useful as a base map. Different methods have already been developed to map bathymetry using remote sensing. Two main groups can be distinguished. One group is using active remote sensing data; the other is based on passive sensor generated multi-spectral information. In this article, the focus is on the passive data method. A modified «depth of penetration» mapping method was implemented on a Landsat7 ETM+-image over Hurghada (Egypt). Some 420 depth measurements were used for ground-truthing and accuracy testing. The accuracy test revealed that the resulting bathymetric map is useful for coral reef mapping, but care should be taken when using it. Deviations from reality were caused by assumptions inherent to the theory used, field sampling, satellite image characteristics and errors during implementation of the method.